(untitled) (Clinics, 2009)
OBJECTIVES: This study analyzes hemodynamic changes in patients with cardiac valvular diseases submitted to dental treatment under local anesthesia containing epinephrine. METHODS: This randomized clinical trial was performed at the Dental Division of the Instituto do Coração do Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo (Brazil). Patients were separated into two groups with the help of an aleatory number table: 2% plain lidocaine (PL, n= 31) and 2% lidocaine with epinephrine (1:100,000) (LE, n= 28). Blood pressure, heart rate, oxygenation and electrocardiogram data were all recorded throughout the procedure. State and trait anxiety levels were measured. RESULTS: Fifty-nine patients were selected for the LE group (n=28), with an average age of 40.3 ± 10.9, or for the PL group (n=31), age 42.2 ± 10.3. No differences were shown in blood pressure, heart rate and pulse oximetry values before, during and after local anesthesia injection between the two groups. State and trait anxiety levels were not different. Arrhythmias observed before dental anesthesia did not change in shape or magnitude after treatment. Complaints of pain during the dental procedure were more frequent within the PL group, which received a higher amount of local anesthesia. CONCLUSION: Lidocaine with epinephrine (1:100,000) provided effective local anesthesia. This treatment did not cause an increase in heart rate or blood pressure and did not cause any arrhythmic changes in patients with cardiac valvular diseases.